Effect of Road Darkness on Young Driver Behaviour when Approaching Parked or Slow-moving Vehicles in Malaysia - Nidzamuddin Md Yusof; Juffrizal Karjanto; Muhammad Zahir Hassan; Syabillah Sulaiman; Abd Fathul Hakim Zulkifli; Ahmad Azad Ab Rashid; Zulhaidi Mohd Jawi; Khairil Anwar Abu Kassim (Automotive Experiences, 2023)
Traffic accidents at night are higher than in other periods, especially on a dark road. This study explores the impact of the dark road on driver behaviours when approaching a parked or slowed-moving vehicle at the front. An experiment was conducted on a racing track at night, with and without road lighting. Different sizes of obstacles were used to represent other vehicles as a lorry, a car, and a motorcycle. The results show that the obstacles can be detected by drivers much earlier with the help of road lighting, and they tend to increase their speed, probably preparing to overtake the obstacles.